Аграрний ринок: поняття та особливості - Лебеденко, Олеся Василівна; Lebedenko, Olesya (Дніпровський державний аграрно-економічний університет, 2020)
Досліджено сутність поняття "ринок". Розглянуто різні підходи до тлумачення поняття "аграрний ринок": підхід, який розглядає аграрний ринок через призму економічних відносин; інституційний підхід; підхід, за якого аграрний ринок розглядається як об'єкт правових відносин. Проаналізовано співвідношення між суміжними поняттями: "аграрний ринок", "агропромисловий ринок", "продовольчий ринок". Встановлено, що згадані поняття слід розмежовувати. Основою для розмежування є об'єкт економічних відносин (товар). Визначено, що властивості та особливості виробництва сільськогосподарської продукції, яка виступає предметом купівлі-продажу на аграрному ринку, обумовлюють специфіку агарного ринку, його відмінності від інших видів ринків, а саме: низька еластичність попиту; циклічність, сезонність пропозиції, її залежність від природно-кліматичних умов; різне призначення сільськогосподарської продукції та ін. Different interpretations of the concept of "market" are studied. The main features of the market, which are the basis of any definition: the market is a certain area of trade, which determines the relationship between producers and consumers and the relationships that have developed between them. Ensuring the realization of the social product, the market creates conditions for the continuous continuation of the process of social reproduction and contributes to the satisfaction of social needs. Different approaches to the interpretation of the concept of "agricultural market" are considered: an approach that considers the agricultural market through the prism of economic relations; institutional approach; an approach in which the agricultural market is considered as an object of legal relations. The relationship between related concepts: "agricultural market" and "agro-industrial market" is analyzed. It is established that the mentioned concepts should be distinguished. The basis for differentiation is the object of economic relations (goods). The agricultural market trades in agricultural products, and the agro-industrial market includes, in addition to agricultural products, also the market of means of production and services. Markets of agricultural products have significant differences from the markets of means of production and services that are part of the agro-industrial market, in terms of operating conditions, infrastructure, investment, lending, regulation, which makes their identification impractical. The relationship between related concepts: "agricultural market" and "food market" is analyzed. It is established that in the essence of the specified markets there are certain differences which demand delimitation of the given concepts. Non-agricultural products may be offered on the food market, while non-food products may be classified as agricultural products. It is determined that the properties and features of agricultural production, which is the subject of sale in the agricultural market, determine the specifics of the agar market, its differences from other types of markets, namely: low elasticity of demand; cyclicity, seasonality, dependence on the natural and climatic conditions of supply; various purposes of agricultural products, etc.
Agricultural market: concepts and features
Keywords: ринок; market; аграрний ринок; agricultural market; агропромисловий ринок; agroindustrial market; продовольчий ринок; food market; сільськогосподарська продукція; agricultural products